Groundwater Contamination and Probabilistic Health Risk Assessment of Heavy Metals in Coal Mining Areas of Punjab, Pakistan - Aima Iram Batool; Muhammad FayyazUrRehman; Naima Huma Naveed; Javaria Ikram; Hakim Bibi (Water, Air, & Soil Pollution, 2026)

Chitosan-crosslinked microwave-engineered biochar alleviates lead stress in Brassica napus by improving soil functioning and plant performance in Pb-contaminated soil - Fakhir Hannan; Yiwa Hu; Ahsan Ayyaz; Muhammad Iqbal; Muhammad Umair Yasin; Iram Batool; Juanjuan Li; Faisal Islam; Yasir Hamid; Muhammad Ahsan Farooq; Weijun Zhou (Journal of Environmental Management, 2026)

Developmental Toxicity of Lead and Copper in Chick Embryos: Morphometric and Histological Assessment of In Ovo Exposure - Aima Iram Batool; Noor Fatima; Muhammad Fayyaz Ur Rehman; Naima Huma Naveed; Javaria Ikram; Iram Inayat (Biological Trace Element Research, 2026)

Mercury exposure in breastfeeding mothers and associated health risks to infants: Evidence from breast milk and nail biomarkers - Reza Dahmardeh Behrooz; Aima Iram Batool; Sanaz Khammar (Food and Chemical Toxicology, 2026)

From roadside soil to cow milk: a potentially toxic metal transfer study using Pennisetum glaucum as fodder - Zafar Iqbal Khan; Natasha Ameer; Asma Ashfaq; Kafeel Ahmad; Muhammad Irfan Ashraf; Ijaz Rasool Noorka; Aima Iram Batool; Ilker Ugulu (Environmental Monitoring and Assessment, 2026)

Evaluation of lead bioaccumulation potential in freshwater snail species as indicators of aquatic pollution in lentic and lotic waterbodies of Sargodha, Pakistan - Ayesha Tariq; Rana Muhammad Ahsan Sajid; Naunain Mehmood; Aima Iram Batool; Hira Muqaddas; Zafar Iqbal Khan (Environmental Monitoring and Assessment, 2026)

Optimization of Tissue Culture Media for Microtuber Development Incorporating Sugars and Zinc Nanoparticles - Muzammil Anwar Khan; Naima Huma Naveed; Aamir Ali; Muhammad Adeel; Aima Iram Batool; Tahir Shahzad; Muhammad Rizwan Khan; Salman Majeed (American Journal of Potato Research, 2026)

Nano-Calcium Enhances Drought Tolerance by Regulating Photosynthesis and Amino Acid Metabolism In Brassica napus - Ahsan Ayyaz; Iram Batool; Tongjun Qin; Kangni Zhang; Weiqi Chen; Zafar Ullah Zafar; Basharat Ali; Muhammad Ahsan Farooq; Fakhir Hannan; Weijun Zhou (Journal of Plant Growth Regulation, 2026)

Hydrothermal synthesis of novel Mn3O4-Nd2O4 nano-hybrid as bi-functional electrocatalyst for water splitting - Muhammad Ibrar; Iram Manzoor; Mostafa A. Ismail; Misbah Shareef; Habiba Batool; Sana Ben Khalifa; Saleh Chebaane; Zeineb Klai (Fuel, 2026)

Wetland Transformation and Waterfowl Decline: Linking Habitat Change to Northern Pintail Losses in Punjab - Nayyar Batool; Aima Iram Batool; Muhammad Fayyaz Ur Rehman; Misbah Sarwar; Javaria Ikram; Naima Huma Naveed; Iram Inayat; Shaheen Riaz; Hakim Bibi (Environmental Management, 2026)

Overexpression of rapeseed BnaLhcb5.3 mediates cellular metabolism and antioxidant defense under chromium stress - Iram Batool; Tongjun Qin; Ahsan Ayyaz; Fakhir Hannan; Muhammad Javed; Weiqi Chen; Zafar Ullah Zafar; Muhammad Shahbaz Naeem; Muhammad Ahsan Farooq; Weijun Zhou (Physiology and Molecular Biology of Plants, 2026)

Cow, Buffalo and Goat Milk as a Pathway for Heavy Metal Exposure from Coal Mining Activities with Spatial and Species-Specific Health Risk Evaluation - Aima Iram Batool; Muhammad FayyazUrRehman; Javaria Ikram; Naima Huma Naveed; Hakim Bibi (Biological Trace Element Research, 2026)

Toxic metal bioaccumulation and health-risk profiling in buffalo milk: a case study from coal mining areas of Chakwal, Pakistan - Aima Iram Batool; Javaria Ikram; Muhammad Fayyaz Ur Rehman; Naima Huma Naveed; Ifrah Zafar; Hakim Bibi (Environmental Geochemistry and Health, 2025)

Biofloc systems as a sustainable strategy to minimize heavy metal bioaccumulation in aquaculture - Ruhma Ihsan; Aima Iram Batool; Muhammad Fayyaz Ur Rehman; Javaria Ikram; Naima Huma Naveed; Iram Inayat; Syed Sikandar Habib (Aquaculture International, 2025)

Nano zero-valent iron engineered with microwave-prepared biochar for improved nickel immobilization in contaminated soil and growth of oil crop (Brassica napus) - Fakhir Hannan; Muhammad Ahsan Farooq; Ahsan Ayyaz; Muhammad Iqbal; Zaid Ulhassan; Kangni Zhang; Faisal Islam; Juanjuan Li; Iram Batool; Weijun Zhou (Journal of Environmental Chemical Engineering, 2025)

Role of aqueous fenugreek (Trigonella foenum-graecum) extract against DBP-induced renal and adrenal pathologies in male rats - Hifsa Shaheen; Sajida Batool; Fatima Iram; Saira Batool; Tahira Almas; Ameer Hamza; Asifa Ijaz; Samar Ambreen; Hafiz Muhammad Uzair (Journal of Molecular Histology, 2025)

Comparative efficacy of imidocarb dipropionate with additive in naturally infected cattle against bovine babesiosis - Sajida Bibi; Sidra Abbas; Muhammad Arfan Zaman; Roquyya Gul; Aima Iram Batool; Iqra Khalil; Arbab Sikandar; Farhan Ahmad Atif (Veterinary Parasitology, 2025)

Transcriptome and Physiological Analyses Unravel Chromium Stress Tolerance Mechanism in Brassica napus L. - Iram Batool; Ahsan Ayyaz; Kangni Zhang; Fakhir Hannan; Yongqi Sun; Tongjun Qin; Habib Ur Rehman Athar; Muhammad Shahbaz Naeem; Muhammad Ahsan Farooq; Weijun Zhou (Journal of Plant Growth Regulation, 2025)

Nettle (Urtica dioica) supplementation: impact on growth, hematology, immune response, and resilience to Aeromonas hydrophila in Labeo rohita fingerlings - Javed Ahmed Ujan; Asif Raza; Syed Sikandar Habib; Rimsha Athar; Osman Sabri Kesbiç; Aima Iram Batool; Syed Fahad Habib; Mohamed Mohany; Francesco Fazio (Veterinary Research Communications, 2025)

Chromium uptake and its impact on antioxidant level, photosynthetic machinery, and related gene expression in Brassica napus cultivars - Iram Batool; Ahsan Ayyaz; Kangni Zhang; Fakhir Hannan; Yongqi Sun; Tongjun Qin; Habib Ur Rehman Athar; Muhammad Shahbaz Naeem; Weijun Zhou; Muhammad Ahsan Farooq (Environmental Science and Pollution Research, 2024)

Correction: Cobalt Uptake by Food Plants and Accumulation in Municipal Solid Waste Materials Compost-amended Soil: Public Health Implications - Zafar Iqbal Khan; Asma Ashfaq; Kafeel Ahmad; Aima Iram Batool; Mehwish Aslam; Tasneem Ahmad; Naunain Mehmood; Ijaz Rasool Noorka; Abdel-Rhman Z. Gaafar; Mohamed S. Elshikh; Syed Sikandar Habib; Riaz Khan; et al. (Biological Trace Element Research, 2024)

Cobalt Uptake by Food Plants and Accumulation in Municipal Solid Waste Materials Compost-amended Soil: Public Health Implications - Zafar Iqbal Khan; Asma Ashfaq; Kafeel Ahmad; Aima Iram Batool; Mehwish Aslam; Tasneem Ahmad; Naunain Mehmood; Ijaz Rasool Noorka; Abdel-Rhman Z. Gaafar; Mohamed S. Elshikh; Syed Sikandar Habib; Riaz Khan; et al. (Biological Trace Element Research, 2024)

Ecological patterns of phytoplankton across lake cross-section: insights into co-evolution of physicochemical conditions in Chashma Lake on Indus River - Huma Ayub; Umar Ijaz; Asif Raza; Amina Zuberi; Nusrat Liaqat; Javed Ahmed Ujan; Syed Sikandar Habib; Aima Iram Batool; Mujeeb Ullah; Khalid Khan; Khayyam Khayyam; Mohamed Mohany (Environmental Monitoring and Assessment, 2024)

Seasonal Variation and Association of Heavy Metals in the Vital Organs of Edible Fishes from the River Jhelum in Punjab, Pakistan - Iram Inayat; Aima Iram Batool; Muhammad Fayyaz Ur Rehman; Khawaja Raees Ahmad; Muhammad Ali Kanwal; Rabiyah Ali; Rameen Khalid; Syed Sikandar Habib (Biological Trace Element Research, 2024)

Calcium Nanoparticles and Abscisic Acid Improve Drought Tolerance, Mineral Nutrients Uptake and Inhibitor-Mediated Photosystem II Performance in Brassica napus - Ahsan Ayyaz; Yingying Zhou; Iram Batool; Fakhir Hannan; Qian Huang; Kangni Zhang; Khurram Shahzad; Yongqi Sun; Muhammad Ahsan Farooq; Weijun Zhou (Journal of Plant Growth Regulation, 2024)

Evaluation of the antibacterial activity and protein profiling of Nile tilapia ( Oreochromis niloticus ) epidermal mucus under different feeds and culture systems (biofloc technology and earthen pond) - Syed Sikandar Habib; Aima Iram Batool; Muhammad Fayyaz Ur Rehman; Saira Naz (Journal of Fish Diseases, 2024)
The mucus layers of fish serve as the main interface between the organism and the environment. They play an important biological and ecological role. The current study focuses on Nile tilapia epidermal mucus reared under different commercial feeds (coded A and B) and environments (biofloc technology and earthen pond systems). Crude protein levels in feed A and B were 30% and 28%, respectively. Water parameters in all culturing systems were suitable for tilapia throughout the study period. The antimicrobial potency of tilapia ( n = 5 from each) epidermal mucus was tested in vitro against human and fish pathogenic strains viz. Staphylococcus epidermidis, Staphylococcus aureus , Escherichia coli, Pseudomonas aeruginosa , Francisella noatunensis , and Aeromonas hydrophila. To determine the antimicrobial activity, zones of inhibition (ZOI) were measured in millimetres and compared with two antibiotics (chloramphenicol and ciprofloxacin). SDS‐PAGE analysis was performed on skin mucus samples of tilapia to determine protein quantity and size (molecular weight). Results of tilapia skin mucus (crude and aqueous) revealed a strong antibacterial effect against all the selected pathogenic strains. However, variation has been observed in the mucus potency and ZOI values between the biofloc and pond tilapia mucus. The crude mucus of tilapia fed on feed A and cultured in the pond exhibited strong antibacterial effects and high ZOI values compared to the mucus of biofloc tilapia, aqueous mucus extracts and positive control chloramphenicol (antibiotic). The SDS‐PAGE results showed that the high molecular weight proteins were found in the collected epidermal mucus of BFT‐B (240 kDa) and EP‐B (230 kDa). Several peptides in fish skin mucus may play a crucial role in the protection of fish against disease‐causing pathogens. Thus, it can be utilized in the human and veterinary sectors as an ‘antimicrobial’ for treating various bacterial infections.

The Effects of Different Carbon Sources on Water Quality, Growth Performance, Hematology, Immune, and Antioxidant Status in Cultured Nile Tilapia with Biofloc Technology - Khalid Hussain Rind; Syed Sikandar Habib; Javed Ahmed Ujan; Francesco Fazio; Saira Naz; Aima Iram Batool; Mujeeb Ullah; Sobia Attaullah; Khayyam Khayyam; Khalid Khan (Fishes, 2023)
The biofloc technology system (BFT) is considered to be one of the sustainable aquaculture systems, which is based on the principle of nutrient recycling with the addition of a carbon source to give dominance to heterotrophic microorganisms. The objective of this study was to evaluate the effect of sugar cane molasses and tapioca flour as carbon sources on the water quality, growth, hematology, immune status, and non-specific antioxidant status of Oreochromis juveniles. Methodologically, the experiment was carried out for 10 weeks on 225 juvenile Nile tilapia with initial body weights of 47.0 ± 1.3 g that were randomly distributed in 09 tanks (1000 L) with a stocking density of 25 tilapias per tank; the treatments were: BFT + SM (S molasses), BFT + TF tapioca flour (TF), and a control with no carbon source added. The control group was fed 100% feed, while the BFT experimental groups were fed microbial flocs along with 75% feed. The results revealed that the water quality parameters were affected by the carbon sources, but were adequate for normal fish welfare, and the biofloc volume was higher (28.94) with the TF carbon source. The growth performance, such as weight gain (98.61), survival (99.01), and improved feed conversion ratio (FCR) (1.69), was recorded in BFT + TF. Significant improvements in WBCs, HCT, HB, lymphocytes, plasma proteins, albumin, and non-specific immune factors (lysozyme activity, immunoglobulins levels, and ACH50) were observed in biofloc-reared fish with tapioca flour as the carbon source compared to the control and sugarcane molasses groups. Moreover, significant increases in catalase (CAT) and superoxide dismutase (SOD) were found in the biofloc-reared fish with different carbon sources. In conclusion, the use of BFT + TF was found to affect improving the water quality, growth, hematology, immunity, and antioxidant status of juvenile Tilapia.

Assessment and Bioaccumulation of Heavy Metals in Fish Feeds, Water, and Some Tissues of Cyprinus carpio Cultured in Different Environments (Biofloc Technology and Earthen Pond System) - Syed Sikandar Habib; Aima Iram Batool; Muhammad Fayyaz Ur Rehman; Saira Naz (Biological Trace Element Research, 2023)

Assessment of Genetic Damage in Coal Miners of Punjab, Pakistan - Fariha Idrees; Aima Iram Batool; Muhammad Fayyaz ur Rehman; Syed Sikandar Habib; Aksa Akram (Biological Trace Element Research, 2023)

Evaluation and Association of Heavy Metals in Commonly Used Fish Feed with Metals Concentration in Some Tissues of O. niloticus Cultured in Biofloc Technology and Earthen Pond System - Syed Sikandar Habib; Aima Iram Batool; Muhammad Fayyaz Ur Rehman; Saira Naz (Biological Trace Element Research, 2023)

Elicitors mediated bio-preservative potential targeting seedless fruits using Capsicum annuum L. (Solanaceae) and Foeniculum vulgare Mill. (Apiaceae) calli extracts - Hamna Batool; Iram Fatima; Naila Safdar; Azra Yasmin (Acta Physiologiae Plantarum, 2023)

Sorptive Capture and Photo-Catalytic Degradation of Methylene Blue from Aqueous Solution Using Lead-Organic Frameworks - Shoomaila Latif; Shamaila Iram; Muhammad Imran; Farah Kanwal; Zafar Iqbal; Aisha Batool; Liviu Mitu (Water, Air, & Soil Pollution, 2021)

Role of resistin genetic variations in knee osteoarthritis pathogenesis, a cross sectional study - Syeda Kanwal Batool Naqvi; Iram Murtaza; Qamar Javed (Molecular Biology Reports, 2019)

Novel Stilbene-triazine Symmetrical Optical Brighteners: Synthesis and Applications - Aamer Saeed; Ghulam Shabir; Iram Batool (Journal of Fluorescence, 2014)